Experimental studies on power control microwave ablation in vitro animal tissues with microwave percutaneous coagulator - Chaichanyut, M.; Lertprasert, P.; Tungjitkusolmun, S. (My University, 2013)
Microwave coagulation therapy (MCT) has been used mainly for the treatment of small-size tumors. The operating frequency is 2450 MHz for the present MCT. In this paper, we analyzed the heating characteristics (temperature distributions patterns, lesion on size and etc.) of an applicator composed of thin microwave antenna. The configurations of thin microwave monopole antennas were considered: Coaxial Quarter Conductor Antennas (CQCA). Experimental protocol was composed by a radiation system and a thermometry system. We apply the microwave power during experiments was 10W, 20W, 40W and 80W which microwave power all case will vary the duration time for ablation were 60s 120s 240s and 480s respectively; Thermal sensors were placed next to the antenna at 1mm, a large number of experiments on porcine liver are carried out, the temperature distribution within the liver are measured and illustrated, for cases of different injected microwave power and ablation time. From our experimental results, if we considered the region where temperature exceeds 50°C, the threshold for successful hepatic ablation. The CQCA has lesion size was larger, with a lesion width of approximately 20 mm. In addition, the ablation areas in cases of different input microwave powers are measured also. All these results indicate the potential validity of this system on medical treatment of liver cancer of human body. © 2013 IEEE.
Keywords: hepatic cancer; in Vitro; Microwave Ablation; Microwave antenna; Porcine Liver; Power control